Carbonated Aggregates and Basalt Fiber-Reinforced Polymers: Advancing Sustainable Concrete for Structural Use - Rabee Shamass; Vireen Limbachiya; Oluwatoyin Ajibade; Musab Rabi; Hector Ulises Levatti Lopez; Xiangming Zhou (Buildings)
In the transition towards a circular economy, redesigning construction materials for enhanced sustainability becomes crucial. To contribute to this goal, this paper investigates the integration of carbonated aggregates (CAs) and basalt fibre-reinforced polymers (BFRPs) in concrete infrastructures as an alternative to natural sand (NS) and steel reinforcement. CA is manufactured using accelerated carbonation that utilizes CO2 to turn industrial byproducts into mineralised products. The structural performance of CA and BFRP-reinforced concrete simply supported slab was investigated through conducting a series of experimental tests to assess the key structural parameters, including bond strength, bearing capacity, failure behavior, and cracking bbehaviour. Carbon footprint analysis (CFA) was conducted to understand the environmental impact of incorporating BFRP and CA. The results indicate that CA exhibits a higher water absorption rate compared to NS. As the CA ratio increased, the ultrasonic pulse velocity (UPV), compressive, tensile, and flexural strength decreased, and the absorption capacity of concrete increased. Furthermore, incorporating 25% CA in concrete has no significant effect on the bond strength of BFRP. However, the load capacity decreased with an increasing CA replacement ratio. Finally, integrating BFRP and 50% of CA into concrete slabs reduced the slab’s CFA by 9.7% when compared with steel-reinforced concrete (RC) slabs.